An Analysis of Fatality Ratios and the Factors That Affected Human Fatalities in the 2011 Great East Japan Tsunami - Suppasri, Anawat; Hasegawa, Natsuki; Makinoshima, Fumiyasu; Imamura, Fumihiko; Latcharote, Panon; Day, Simon (Frontiers in Built Environment, 2016)
This study presents a new analysis of spatial variation in fatality ratios in the 2011 Great East Japan tsunami, in order to overcome the limitations of previous studies that tended to underestimate the fatality ratios. In addition, this analysis was performed in a manner that allows the results to be compared to those from analyses of fatality ratios in other historical tsunamis. To do this, it uses population and fatality data at the village scale in areas of less than 3 km2 where the inundation ratio was greater than 70%, rather than the lower resolution data used in previous studies. The median value of the tsunami inundation depth at each location was extracted at the original 5-m grid resolution. All of the data were obtained from the Reconstruction Support Survey Archive. Based on the results, a strong correlation between the fatality ratio and inundation depth was found only in some areas of the Sendai Plain, whereas no strong correlation was observed along the Sanriku ria coastline. Fatality ratios in Sanriku were likely related not only to the force of the tsunami but also to other factors, such as the ria topography and the population’s experience of past historical tsunamis. Data from other tsunamis in regions where tsunamis frequently occur also indicate that historical tsunami experience is a key factor in reducing fatality ratios. In contrast, the Sendai Plain shows smaller variation in local tsunami amplification effect compared to that of the Sanriku ria coastline as well as fewer coastal defense structures. Therefore, the fatality ratio in that region was predominantly affected by the force of the tsunami and the residents’ individual characteristics. On the Sendai Plain, Ishinomaki City exhibited a strong correlation between the fatality ratio and inundation depth as well as between fatality ratio and building damage, because its low evacuation ratio meant that many fatalities occurred in victims’ homes. Therefore, the fatality ratio in Ishinomaki City was higher than those in other areas at the same inundation depth. Simple empirical formulas were developed for estimation of human fatalities based on inundation depths and building damage ratios.